Information technologies and nursing process records: case study at a neonatal ICU - Raphael Brandão Pereira; Maria Alice Coelho; Maria Márcia Bachion (Universidade Federal de Goias, 2016)
The objective of this study was to analyze the recording of the nursing process, supported by information and communication technologies in both printed and electronic media in the neonatal intensive care scenario. This case study was exclusive, integrated, and conducted between January and April 2014. The study counted on the participation of seven nurses who worked at a neonatal ICU before and after the deployment of new information and communication technologies, which combined electronic and physical (paper) support. Data were collected from medical records and a questionnaire answered by the nurses. Simple and percentage frequency in the levels of the nursing process application were used for analysis, as well as the set of intervening factors related to the work organization structure and process. Positive and negative results were seen, as well as intervening factors. The study concluded that the new information and communication technologies delivered in physical materials accounted for the registration of the higher number of records in the data collection and that the registration of the other stages did not show any substantial improvement.